Helicobater pylori infection in Turkish preschool and school children: Role of socioeconomic factors and breast feeding - (:unkn) unknown (My University, 2003)
It has been shown that Helicobacter pylori (H. pylori) infection is rare among children in developed countries. In Turkey, the prevalence of H. pylori infection among adults is about 80-85%, which is close to the ratios reported in developing countries. There is limited knowledge, however, on the prevalence, determinants and associations of this infection, such as short stature, familial history of dyspepsia and abdominal pain, in children. The aims of this study were to estimate the prevalence, determinants and associations of H. pylori infection in a group of healthy school children using 13C-urea breath test (13C-UBT). The study subjects were selected from a kindergarten and an elementary school. The H. pylori status was determined by 13C-UBT. Standard questionnaires ascertaining sociodemographic data were completed for each child by questioning the mothers. Three hundred twenty-seven children aged 3-12 years participated in the study. Overall, 162 children (49.5%) were infected with H. pylori, and the prevalence increased with age: 18.2% under 4 years, 41% at 4-6 years, 48.6% at 6-8 years, 50% at 8-10 years, and 63% at 11-12 years of age. No association was determined between H. pylori infection and height and weight percentiles, history of abdominal pain or family history of dyspepsia in the study group. Investigation of the prevalence of H. pylori infection in our study group in relation to socioeconomic data in a logistic regression model revealed that low income, high household density of children, use of stove for heating, and no breast feeding were important risk factors for H. pylori infection. This study was done in a group of healthy Turkish children to estimate the age-related prevalence of H. pylori infection and to determine the factors predisposing to H. pylori infection during childhood. It was found that 1/5 of healthy Turkish children were infected with H. pylori before four years of age, and that every one child out of two under 11 years of age was infected with H. pylori. Low socioeconomic status, poor household living conditions and no breast feeding were determined as independent risk factors of H. pylori infection.
Keywords: Children; Helicobacter pylori; Prevalence